Skilled construction workers in the construction industry: Workers certification dilemma?. Issue 4 (April 2020) - Widaningsih, L; Hamdani, A; Krisnanto, E; Susanti, I; Kusuma, Y
Abstract: This paper aims to provide an overview of the complicated problem of skilled workers in the construction industry faced with the demands of worker certification. The skilled workers in question are the ones at the construction sites or known as construction workers (builders). The number of groups of workers continues to increase every year along with the development of the country's construction industry which also increases in quantity. However, of the more than 8.3 million construction workers spread across various construction projects, only 7.4% are certified. This study uses descriptive qualitative methods with interview techniques, Focus Group Discussion (FGD), and document analysis. This research found that there was a large gap between the demands of modern industry on construction workers and the prerequisites for skills certification, and it became a major problem in the employment system in the construction industry. The contributing factors are the traditional work culture, lack of knowledge and information in worker certification, the institutional certification system, the difficulty of access to education and training to develop skills and gain recognition as indicated by increased welfare regarding minimum wages.